A one-year review of macrosomic births at the Cantonal Hospital Zenica, Bosnia and Herzegovina - Hana Štimjanin; Rasim Iriškić; Jasmin Hodžić; Ena Štimjanin (Medicinski glasnik, 2019)
Aim: To identify a rate of macrosomic births in a one-year review, associated maternal characteristics and pregnancy outcome. Methods: This one-year retrospective review included all macrosomic deliveries at the Department of Obstetrics and Gynaecology at the Cantonal Hospital Zenica between 1 January 2018 and 31 December 2018. The data were collected from maternal and newborn medical records. A total of 361 singleton normal birth weight term newborns (birth weight < 4000 g, but not small for gestational age) who were delivered in the same period, represented the control group. Results: Among the total of 2758 women who gave birth, 360 (13.05%) macrosomic infants (birth weight more than 4000 g) were delivered. Mean birth weight was 4258.90 g (maximum 5460g); nine (0.33%) were >5000g. Male macrosomic infants were more frequently represented, 245 (68,1%) comparing to the control group (p<0.01); in the control group female infants were more frequently represented (p<0.01). The overall Cesarean section rate, including elective Cesarean delivery was 23.2%, and 76.1% underwent an attempt of labour delivered vaginally. Conclusion: Macrosomia represents a risk for adverse outcome for the mother and neonate, with a higher risk for the operative mode of delivery.
Keywords: birth weight; delivery; fetal macrosomia; fetal outcome; pregnancy